Fast Charging Anode Materials for Lithium‐Ion Batteries: Current Status and Perspectives. (25th March 2022) - Li, Shengqiang; Wang, Kai; Zhang, Gefei; Li, Shani; Xu, Yanan; Zhang, Xudong; Zhang, Xiong; Zheng, Shuanghao; Sun, Xianzhong; Ma, Yanwei
Abstract: With the enormous development of the electric vehicle market, fast charging battery technology is highly required. However, the slow kinetics and lithium plating under fast charging condition of traditional graphite anode hinder the fast charging capability of lithium‐ion batteries. To develop anode materials with rapid Li‐ions diffusion capability and fast reaction kinetics has received widely attentions. This review summarizes the current status in the exploration of fast charging anode materials, mainly including the critical challenge of achieving fast charging capability, the inherent structures and lithium storage mechanisms of various anode materials, as well as the recent progress to improve the rate performance involving morphology regulation, structure design, surface/interface modification, as well as forming multiphase systems. Finally, the challenges and future directions of developing fast charging Li‐ion batteries are highlighted. Abstract : This review summarizes the current status in the exploration of fast charging anode materials, mainly including the critical challenge of achieving fast charging, the inherent structures and lithium storage mechanisms of various anode materials, as well as the recent progress to improve the rate performance involving morphology regulation, structure design, surface/interface modification, as well as forming multiphase systems.